Are anterior cruciate ligament-reconstructed athletes more vulnerable to fatigue than uninjured athletes? - Smeets, A.; Vanrenterghem, J.; Staes, F.; Vandenneucker, H.; Claes, S.; Verschueren, S. (Medicine & Science in Sports & Exercise, 2020)
Introduction Fatigue has a negative impact on lower extremity neuromuscular and biomechanical control. Because anterior cruciate ligament reconstruction (ACLR) athletes show already neuromuscular/biomechanical deficits in an unfatigued state, the negative impact of fatigue may magnify these deficits or help expose other deficits. So far, this has only scarcely been assessed warranting further research. Methods Twenty-one athletes who had an ACLR and 21 uninjured controls performed five unilateral landing tasks before and after a match simulation protocol, whereas muscle activation (vastus medialis, vastus lateralis, hamstrings medialis, hamstrings lateralis, gastrocnemius medialis, gastrocnemius lateralis, gluteus medius) and landing kinematics and kinetics of the hip, knee, and ankle joint were recorded. A two-way ANOVA with a mixed-model design (main effects for group and fatigue) was used to compare landing kinematics, kinetics, and muscle activation between groups, and prefatigue and postfatigue. To avoid unjustified reduction of the data to discrete values, we used one-dimensional Statistical Parametric Mapping. Results Only two interaction effects were found: an increased postfatigue knee abduction moment and an increased postfatigue thorax flexion angle was found in the ACL injured legs but not in the uninjured legs of the ACL group or in the control group, during the lateral hop and the vertical hop with 90° medial rotation, respectively. Conclusions This study showed that overall ACLR athletes and uninjured athletes have similar biomechanical and neuromuscular responses to fatigue. For two biomechanical parameters, however, we did find an interaction effect, suggesting that landing deficits in ACLR athletes may become clearer in certain tasks when fatigued.